Investment process and the ways to reduce the duration of investment construction projects - Zeltser, R.; Zeltser, Y. (Ways to Improve Construction Efficiency, 2023)
The urgent task of the state is to intensify investment activities and significantly increase the volume of investments. The general legal, economic and social conditions of investment activity on the territory of Ukraine are defined by the Law of Ukraine "On Investment Activity", which is aimed at ensuring equal protection of the rights, interests and property of subjects of investment activity regardless of the forms of ownership, as well as at effective investment of the economy of Ukraine. development of international economic cooperation and integration. The investment process means constant and growing investment of capital in material production for the purpose of successful social and economic development of Ukraine. For construction, the investment process means the creation of specific objects (or their complexes) for production and non-production purposes in the interests of specific investors (investor). The investment process consists of the implementation of separate investment construction projects (ICP). Each ICP is characterized by the duration of the life (or investment) cycle, which is measured by the interval of calendar time from the date of making the investment decision to the moment when the project goal is achieved. There are three stages of this cycle: justification of the idea and planning of investment, development of funds, reimbursement of invested funds or achievement of the project goal. The article examines the main, key procedures of each stage, which emphasize the importance of solving the financing issue, since the full set of procedures depends on the scope of the project. Reducing the duration of the investment cycle of a construction project depends on the intensification of each of its stages. The main factors affecting the reduction of the duration of each stage of the investment cycle of the construction project are given. The results of the conducted research should be taken into account in the further improvement of the legislative acts of Ukraine in order to activate investment activities and significantly increase the volume of investments in Ukraine.